2003
DOI: 10.1177/08830738030180110501
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Prospective Study (Clinical Spectrum) of Childhood Guillain-Barré Syndrome in the Arabian Peninsula: Comparison of Outcome in Patients in the Pre— and Post—Intravenous Immunoglobulin Eras

Abstract: A prospective study of Guillain-Barré syndrome from January 1992 to December 2001 was undertaken. Intravenous immunoglobulins were used in all patients. All patients were followed up until complete recovery. Various parameters, such as onset of weakness, duration of hospital stay, ventilation requirement, residual deficit, and mortality, were recorded. Acute relapses and fluctuations were also noted. The pattern of this group was compared with patients before 1992, who were not given intravenous immunoglobulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
1
18
0
1
Order By: Relevance
“…16 At the same time the mean hospital stay in the IVIG group was markedly reduced, though the range was not different. Complete recovery was also faster in terms of both mean time and longest time in the IVIG group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…16 At the same time the mean hospital stay in the IVIG group was markedly reduced, though the range was not different. Complete recovery was also faster in terms of both mean time and longest time in the IVIG group.…”
Section: Discussionmentioning
confidence: 96%
“…11,12,13 However, there are few reports with an unfavorable response to IVIG. 14,15,16 Plasmapheresis was done in two of our patients who failed to respond to IVIG and needed ventilation. Although some authors advocate that plasmapheresis is superior to IVIG in severe cases, 15 many studies favour IVIG, 11,12,13 based on the fact that the group who underwent plasmapheresis had higher relapse rate as compared to the IVIG group.…”
Section: Discussionmentioning
confidence: 98%
“…[7] Since the first report of GBS in childhood by Mannier-Vinard in 1925, showing an incidence of 0.24–1.26 per 100,000 children under 15 years of age,[9] the age-specific incidence was 1.26 in 100,000 in the 1–4 years age group and 0.24 in 100,000 in the 5–9 years age group. [12] GBS has a worldwide distribution and affects all races and all ages, including the newborn.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of acute GBS was based on the following criteria: An acute progressive symmetric weakness of the extremities with areflexia or hyporeflexia, CSF showing albuminocytological dissociation and electrophysiology revealing features of demyelinating/axonal neuropathy. [9] Albuminocytological dissociation was defined as CSF with raised protein and total cell count of ≤10/mm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Pediatric studies of IVIG (2 g/kg divided over 2 or 5 days) are limited but suggest benefit [25]. One multicenter randomized study from Western Europe found that early treatment with IVIG was associated with earlier motor recovery [31]. Other studies show that IVIG was no better than supportive care, although the time from symptom onset to maximum symptom severity was shorter in patients who received IVIG within 10 days than patients who did not receive IVIG [32].…”
Section: The Therapeutic Role Of Ivigmentioning
confidence: 95%